Natural Resources Management in African Agriculture: Understanding and Improving Current Practices 2002
DOI: 10.1079/9780851995847.0115
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry adoption decisions, structural adjustment and gender in Africa.

Abstract: This paper shows that, under certain conditions (i.e., land availability and unaffordable fertilizer), improved fallows are potentially gender-neutral, scale-neutral soil-fertility technologies adoptable by women as well as by men, and by the poor and food-insecure as well as the food secure. The evidence comes mainly from eastern Zambia, where in 4 ICRAF villages an almost equal amount of female-headed households (47%) and men in male-headed households (52%) have adopted improved fallows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This is probably because some BNF technologies, such as crop rotation with legumes, leguminous cover crops, and improved fallows may reduce profits per hectare in the near term by using land for lower-return crops or fallows, and are thus less likely to be adopted by households with little land. This explanation is consistent with our results in Chapter 4, showing lower current returns on plots where crop rotation is used, and with the results of numerous studies on the constraints to adoption of leguminous cover crops and agroforestry technologies (for example, Adesina and Chianu 2002;Gladwin et al 2002;Place et al 2002a).…”
Section: Determinants Of Soil Nutrient Inflowssupporting
confidence: 92%
“…This is probably because some BNF technologies, such as crop rotation with legumes, leguminous cover crops, and improved fallows may reduce profits per hectare in the near term by using land for lower-return crops or fallows, and are thus less likely to be adopted by households with little land. This explanation is consistent with our results in Chapter 4, showing lower current returns on plots where crop rotation is used, and with the results of numerous studies on the constraints to adoption of leguminous cover crops and agroforestry technologies (for example, Adesina and Chianu 2002;Gladwin et al 2002;Place et al 2002a).…”
Section: Determinants Of Soil Nutrient Inflowssupporting
confidence: 92%
“…Such households would need guidance on adopting technologies that are potentially gender-neutral, for example, improved fallows. Studies by ICRAF in eastern Zambian villages (Gladwin et al 2002) and other studies from Malawi, Zimbabwe and Kenya (Thangata, et al 2007;Quisumbing and McClafferty, 2006) have shown female-headed households to be equally competent in adopting particular agroforestry systems. While such is the case, it remains important to emphasise the need for careful selection of technologies to arrive at those that suit the conditions of disadvantaged households.…”
Section: Women-headed Householdsmentioning
confidence: 99%
“…Several studies (e.g. Gladwin et al, 2002;Keil et al, 2005) found no significant differences between the proportions of female-and male-headed households planting improved tree fallows. Other studies found that men in the region control many household decisions including those involving cash transactions and hence, although women may be using the technology as commonly as men, they may not be benefiting from it as much.…”
Section: The Number Of Hectares Covered By New Technologies or Practicesmentioning
confidence: 99%